Integrated multidisciplinary approach in a case of occupation related planned complex suicide-peticide. (February 2021) - Palazzo, Chiara; Pascali, Jennifer Paola; Pelletti, Guido; Mazzotti, Maria Carla; Fersini, Federica; Pelotti, Susi; Fais, Paolo
Highlights: A case of complex suicide associated to the killing of a pet is presented. The term peticide, as the combination of "pet" and "homicide" is proposed. Two different suicide methods, intoxication and strangulation have been identified. An occupation related suicide was supposed in light of victim's professional skills. Abstract: The combined event of a suicide and the killing of a pet has been hardly explored in forensic literature, but it is not rare at all. In the reported case the dead corpse of a 60-year old mentally ill woman and the carcass of a dog were found on the bed of a private apartment. In light of death scene investigation, necroscopic examination and toxicological analyses death was attributed to licit drug intoxication and self-strangulation after lethal poisoning of the dog. Due to the presence of two lethal means (cervical noose and drugs), acting in chronological order, the event was classified as a secondary complex suicide. Moreover, the woman, although mentally ill, was a psychiatrist. Thus, her professional background, namely the easy access to psychiatric drugs together with her knowledge of drug composition and properties lead to suppose an occupation related suicide. The comprehensive analysis of all the available information, including death scene investigation, occupational, necroscopic and toxicological data, resulted of the utmost importance for a proper reconstruction of the events and are recommended in complex cases such as occupation related planned complex suicides combined to the killing of pets.